2015
DOI: 10.3109/09273972.2015.1025986
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Persian Version of the Adult Strabismus Questionnaire and Evaluating the Effect of Strabismus Surgery on Health-Related Quality of Life

Abstract: Our version might be appropriate for evaluating HRQOL of the patients with strabismus. The significant increase in the total and subscale scores after strabismus surgery showed the importance of strabismus surgery in improving HRQOL of the patients, especially in psychosocial aspects. The strabismus surgery might have a greater benefit in improving HRQOL of the female patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Few studies on Rb patients have been conducted regarding strabismus in patients with salvaged globes and the prevalence and features of strabismus have mostly been mentioned descriptively [ 12 , 13 ]. Strabismus has significant effects on the health-related quality of life (HRQOL) of the patients [ 14 , 15 ]. People with strabismus live with more clinical anxiety or depression compared to the general population and the levels of social anxiety and social avoidance were significantly poorer than population norms [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies on Rb patients have been conducted regarding strabismus in patients with salvaged globes and the prevalence and features of strabismus have mostly been mentioned descriptively [ 12 , 13 ]. Strabismus has significant effects on the health-related quality of life (HRQOL) of the patients [ 14 , 15 ]. People with strabismus live with more clinical anxiety or depression compared to the general population and the levels of social anxiety and social avoidance were significantly poorer than population norms [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the reconstructive realignment of eyes and psychological benefits once the ocular alignment is restored, strabismus surgeries may be restoration of binocular single vision, binocular visual field expansion and unexpected recovery of sensory fusion [ 15 , 16 ]. However, due to low vision in most involved eyes, we could not report the improvement in the sensory functions after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Age did not affect the results, but females and ETs reported greater improvements in psychosocial functioning compared to males and XTs. Greater improvements in HRQoL in females postoperatively has also been reported using the AS-20 (Akbari et al 2015;Alam et al 2014;Glasman et al 2013). Xu et al (2012) used their own questionnaire to investigate social and psychological effects of strabismus and surgical correction.…”
Section: Questionnairesmentioning
confidence: 97%
“…In those without diplopia, successful outcomes had significantly higher VFQ-25 scores (composite score, all vision-specific subscales, driving subscale, and colour vision subscale) . Akbari et al (2015) reported good correlation between the AS-20 and VFQ-25 (Persian versions) but did not analyse their results based on surgical success. Jackson et al (2006) used visual analogue scales to report coping, lifestyle, worry, noticeable strabismus, and strabismus severity on a 0-10 scale, as well as the DAS-24, HADS and the WHOQoLBref.…”
Section: Visual Functionmentioning
confidence: 99%